Pliocene origin, ice ages and postglacial population expansion have influenced a panmictic phylogeography of the European bee-eater Merops apiaster - Moura, Carina Carneiro de Melo; Bastian, Hans-Valentin; Bastian, Anita; Wang, Erjia; Wang, Xiaojuan; Wink, Michael (Diversity, 2019)
Oscillations of periods with low and high temperatures during the Quaternary in the northern hemisphere have influenced the genetic composition of birds of the Palearctic. During the last glaciation, ending about 12,000 years ago, a wide area of the northern Palearctic was under lasting ice and, consequently, breeding sites for most bird species were not available. At the same time, a high diversity of habitats was accessible in the subtropical and tropical zones providing breeding grounds and refugia for birds. As a result of long-term climatic oscillations, the migration systems of birds developed. When populations of birds concentrated in refugia during ice ages, genetic differentiation and gene flow between populations from distinct areas was favored. In the present study, we explored the current genetic status of populations of the migratory European bee-eater. We included samples from the entire Palearctic-African distribution range and analyzed them via mitochondrial and nuclear DNA markers. DNA data indicated high genetic connectivity and panmixia between populations from Europe, Asia and Africa. Negative outcomes of Fu’s Fs and Tajima’s D tests point to recent expansion events of the European bee-eater. Speciation of Merops apiaster started during the Pliocene around three million years ago (Mya), with the establishment of haplotype lineages dated to the Middle Pleistocene period circa 0.7 Mya. M. apiaster, which breed in Southern Africa are not distinguished from their European counterparts, indicating a recent separation event. The diversification process of the European bee-eater was influenced by climatic variation during the late Tertiary and Quaternary. Bee-eaters must have repeatedly retracted to refugia in the Mediterranean and subtropical Africa and Asia during ice ages and expanded northwards during warm periods. These processes favored genetic differentiation and repeated lineage mixings, leading to a genetic panmixia, which we still observe today.
Gesehen am 24.06.2019